Proximal kissing stent extensions after stent therapy of the proximal external and internal iliac artery at the iliac bifurcation for recurrent claudication and erectile dysfunction - Mikolaj Walensi, MD; Kai Nassenstein, MD; Jonas Hensel, MD; Gundula Schulz, MD; Fadi Alaid, MD; Nikolaos Tsilimparis, MD; Barbara Rantner, MD; Johannes N. Hoffmann, MD (Radiology Case Reports, 2025)
Atherosclerotic pathologies in the pelvic vessels can lead to typical claudication of the legs in the case of the common and external iliac artery (EIA), and to rarer complaints like gluteal claudication or erectile dysfunction when the internal iliac artery (IIA) is affected. In the case of a symptomatic disease of both arteries, the indication for a revascularization can be highly justified, especially if the contralateral IIA is occluded. We report the case of a 57-year-old male patient who, after initial stent therapy of the proximal EIA and IIA of the right side, presented again with right leg pain and erectile dysfunction. High-grade in-stent stenoses were treated with extension of both stents using the kissing stent technique, leading to symptom improvement without complications. Both, the stent technique itself and re-interventions in kissing stent technique at the iliac bifurcation are excellent treatment options for atherosclerotic pathologies in the iliac arteries. They can be of benefit to the patient, especially in cases of high levels of suffering and to avoid more extensive, open surgical procedures.